Differences in the HbA1c‐lowering efficacy of glucagon‐like peptide‐1 analogues between Asians and non‐Asians: a systematic review and meta‐analysis. Issue 10 (15th April 2014) - Kim, Y. G.; Hahn, S.; Oh, T. J.; Park, K. S.; Cho, Y. M.
<x xml:space="preserve">Abstract</x> Aims To compare the HbA1c‐lowering efficacy of glucagon‐like peptide‐1 (GLP‐1) analogues between Asians and non‐Asians with type 2 diabetes. Methods We searched randomized controlled trials from MEDLINE, EMBASE, LILACS, CENTRAL and ClinicalTrials.gov. Studies described in English were included if the treatment duration was 12 weeks or more, information about ethnicity and baseline HbA1c values were available and a GLP‐1 analogue was compared with a placebo. For the ethnic comparison, we divided the studies into Asian‐dominant studies (≥50% Asian participants) and non‐Asian‐dominant studies (<50% Asian participants). Results Among the 837 searched studies, 15 trials were included for the meta‐analysis. The weighted mean difference of HbA1c with GLP‐1 analogues was −1.16% [95% confidence interval (CI) −1.48, −0.85] in the Asian‐dominant studies and −0.83% (95% CI −0.97, −0.70) in the non‐Asian‐dominant studies. The between‐group difference was −0.32% (95% CI −0.64, −0.01; p = 0.04). The relative risk (RR) with 95% CIs for achieving the target HbA1c ≤7.0% tended to be greater in the Asian‐dominant studies [RR 5.7 (3.8, 8.7)] than in the non‐Asian‐dominant studies [RR 2.8 (2.4, 3.3)]. Body weight changes were similar between the two groups. Hypoglycaemia tended to be more common in Asian‐dominant studies (RR 2.8 [2.3, 3.5]) than in non‐Asian‐dominant studies (RR 1.5 [1.2, 1.8]), but severe hypoglycaemia was very rare in both groups. Conclusion GLP‐1 analogues lower HbA1c more in Asian‐dominant studies than in non‐Asian‐dominant studies. Further studies are warranted to explore the potential mechanisms of the ethnic difference.